The demographic impacts of the agro-export model in Argentina - Manzano, Fernando Ariel; Velázquez, Guillermo Ángel (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2021)
After the arrival of the Spanish conquerors and during two centuries of the reign of its monopoly, the entrance was not allowed for foreigners, and the population remained distributed in the regions, in almost inverse proportions to the current ones. With the fall of the Spanish regime and the advances of the English monopoly, the Argentine territorial center began to shift from the Northwest to the Littoral and to produce variations in the demographic dynamics. The establishment of the agro-export model produced an exceptional influx of immigrants from overseas, which generated vertiginous changes in the structure of the population. In the same way, the end of the agro-export model that caused an abrupt interruption of the overseas immigration flow, generated an intense demographic change that has affected the population structure to date. This article focuses on the migratory movement produced by the agro-export model, intending to analyze its effects on the rate of population growth, on the distribution of basic demographic variables —sex and age— and changes in the distribution using the national population censuses carried out to date as the main source.